Testing of high strength aluminium alloy SHS and RHS stub columns in fire. (1st June 2023) - Han, Qinghua; Li, Mengyu; Wang, Zhongxing
Highlights: 24 tests on high strength aluminium alloy stub columns in fire conducted. Local buckling response of high strength aluminium alloy stub columns in fire investigated. Current design methods for aluminium alloy stub columns in fire evaluated. FE models replicating local buckling of aluminium alloy columns in fire created and validated. Abstract: With the aim of investigating the local buckling behaviour of high strength aluminium alloy columns in fire, six room-temperature tests and eighteen steady-state tests at elevated temperatures on 7A04-T6 aluminium alloy square hollow section (SHS) and rectangular hollow section (RHS) stub columns were conducted in this study. Initial geometric imperfections of each specimen were first measured by the 3D laser scanner. Then, the test setup, procedure and instrumentation are fully reported. Test results, including failure modes, ultimate resistances and load-end shortening curves were obtained and utilised to evaluate the accuracy of current design methods for aluminium alloy stub columns in fire. The evaluation indicated that European and Chinese codes provided rather conservative predictions at 400 °C, while most of the resistances predicted by the American specification and methods proposed by Maljaars et al. were on the unsafe side. New design approaches proposed by the authors obtained more accurate and less scattered resistance predictions. Furthermore, the finite element (FE) models were also established and achieved good agreements with the test results.